(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Nowadays people are looking for new products that will definitely love. The researchers decided to choose “buchi” for the person that is not popularly known among other people. They came up with an innovation to make it more delicious by adding some flavor into it, and possibility to be known in the food industry. The researchers conducted with 50 respondents, 27 Females and 23Males mostly students and employees from different schools and establishment Said survey was done in Barangay Kaligayahan, Quezon, City. There was also food tasting within the vicinity. The researches conduct a survey, 44 out of 50 people which is 80% of the respondents prefer to eat chocolate flavored buchi and all of them which is 100% of the respondents would like to spend 20php for the product. The proponents choose their location because it is accessible to customers, many passers-by and it is surrounded by many establishments. We made more promotions to better identify our product. The researcher assured that our sales will increase over the year. Sales monitoring should be done to find out the business profit. Given the proper time frame of the working hours and well with the rest period, the workers will surely be motivated to attend to their task. The researchers make new products, and they conducting a survey and as far as the product is concerned, the company must be consistent with its quality so that it will be easily and continuously acceptable in the market. Price affordability should also be given a consideration. Excess ingredients should be set aside be utilized for the next production to avoid financial loss.